Mitigating Subsynchronous Resonance in Doubly Fed Wind Turbine Induction Generator Using FACTS Devices: A Comparative Case Study - Phuong, Bui Thi Hoa; Ngoc, Tran Thanh; Thanh, Pham Hong; Dai, Le Van (Association for Scientific Computing Electronics and Engineering (ASCEE), 2025)
Sub-synchronous resonance (SSR) may result from the recent integration of wind power generating systems (WPGS) based on double-fed induction generators (DFIG) into weak grids using long transmission lines with series capacitor adjustment. The amount of series compensation used in the transmission line determines how much SSR affects the grid, which may lead to serious instability. Flexible alternating current transmission system (FACTS) devices, which aid in controlling and stabilizing grid oscillations, are a workable way to lessen the impacts of SSR. In order to analyze the efficacy of FACTS controllers in mitigating SSR, this work examines the modeling and control techniques of WPGS-DFIG employing Thyristor controlled series capacitor (TCSC), static Var compensator (SVC), and static synchronous compensator (STATCOM). Time-domain simulations on a modified IEEE First benchmark, with varying series compensation levels and grid fault circumstances, are used to verify the study's correctness and effectiveness. According to the simulation findings, the STATCOM controller mitigates SSR far more effectively than TCSC and SVC. The STATCOM controller optimizes the performance of the WPGS-DFIG system by increasing dynamic responsiveness and grid stability in SSR-prone conditions.